Analisis Kebijakan Penetapan Harga Sembako di Kota Bengkulu Perspektif Ibnu Taimiyah - Wahyu Trijati; Khairiah Elwardah; Makmur (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to identify how the pricing policy in Bengkulu City is and to understand how the pricing policy for basic necessities in Bengkulu City is from Ibn Taimiyah's perspective. The study was conducted with a qualitative approach through the use of secondary data as a collection technique that was collected indirectly from various written references, such as documents, relevant data related to research, books, and various media, journals and other sources related to Ibn Taimiyah. From the research and discussion, it was found that in Bengkulu City, the pricing of basic necessities is implemented through the 4K strategy, namely maintaining price affordability, ensuring supply availability, facilitating distribution, and implementing effective communication. The Bengkulu City Government also routinely holds market operations to monitor price stability and prevent hoarding and speculation practices. And also Ibn Taimiyyah's thoughts regarding pricing policies have strong relevance in the current context in Bengkulu City. According to him, price fluctuations are not always the result of trader injustice. Price increases can be caused by decreased production, disruption of supply from outside the region, or a spike in demand that is not comparable. However, if there are manipulative practices such as hoarding of goods, fraud, or market control by a group of business actors for personal gain, then government intervention is mandatory in order to restore market balance and justice.